Analysis on the effect of different X-bracing arrangements and locations on lateral drift of different storey steel frame buildings subjected to lateral forces using ANSYS - Tan, Woon Han (2017)
Wind had caused to structural failures in the past 150 years and most of the building failures caused by wind happened while the erection of steel frame. For a high rise building that carry lateral loads from wind, braced frame was used to resist the wind loads as it was able to reduce the lateral drift of high rise building effectively. This study was aim to determine the effect of varying the position of x-bracing, joint connection which was pin and fixed connection to the drift index, and different storey steel frame building to the lateral drift. There were total of 35 models of 28-storey steel frame in term of different arrangements of the bracing involved in this study by using ANSYS. After that, the optimum arrangement and location of bracing was chosen then apply to 24, 20 and 16-storey building to observe the lateral drift. It was followed by changing the pin connection from optimum location and arrangement of bracing for 28- storey to fixed connection in order to observe which type of connection provides the best stability to the steel frame. Finally, it was known that the exterior bay bracing along with the floors bracing near to each other and located at the middle of the steel frame provided the best stability to the steel frame.